2013
DOI: 10.1590/s1809-29502013000200008
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de 20 sessões do método Pilates no alinhamento postural e flexibilidade de mulheres jovens: estudo piloto

Abstract: | The aim of this study was to evaluate the effects of the Pilates method on the postural alignment and joint flexibility in healthy young females. Thirty-three women aged between 18 and 30 years (56.8±8.5 kg, 1.60±0.06 m, and 22.1±2.7 kg/m 2 ) having no prior knowledge of Pilates participated in this study. They were randomly allocated into two groups: control group (without intervention) and Pilates group (PG; mat Pilates, 20 sessions, twice a week). Pre and post-program evaluation procedures were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
29

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 28 publications
1
26
0
29
Order By: Relevance
“…In children, incorrect postural habits, due to long periods in sitting posture, oversized seats, inadequate or poorly executed exercises, and heavy backpacks, result in postural disorders since the early years of schooling 5 . Furthermore, the children's body mechanics is in process of growth and their musculoskeletal structures are under development, being more susceptible to deformation 6 . Correct posture in infancy or early detection of postural disorders enable body alignment as an adult, since that period is essential for an individual's musculoskeletal development, with greater possibilities for prevention and treatment of such postural alterations, especially concerning the spinal column 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children, incorrect postural habits, due to long periods in sitting posture, oversized seats, inadequate or poorly executed exercises, and heavy backpacks, result in postural disorders since the early years of schooling 5 . Furthermore, the children's body mechanics is in process of growth and their musculoskeletal structures are under development, being more susceptible to deformation 6 . Correct posture in infancy or early detection of postural disorders enable body alignment as an adult, since that period is essential for an individual's musculoskeletal development, with greater possibilities for prevention and treatment of such postural alterations, especially concerning the spinal column 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In the context of postural re-education, it is known that the Pilates Method contributes positively to postural alignment of the body 6 , as this technique is based on exercises that combine strength, stretching, and breathing, which presuppose improvement in posture, in addition to physical and mental conditioning. In fact, a study confirms that the Pilates method contributes positively to body posture in young, healthy women 9 ; however, its effect on healthy children in school age is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results reported in Chart 1 and Table 2, we may affirm that there is no scientific evidence to promote the use of Pilates Method for women's posture alignment benefits. Although, among the four studies reviewed, two high-quality studies have shown that the method is able to promote general effects on posture alignment 18,20 ; and a high-quality study found no changes 7 . Hence, results are conflicting.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…The study that obtained the lowest value was considered of low quality 19 . Remaining studies 7,18,20 were considered of high quality; the criteria more frequently met were the subject's distribution randomness, similarity and initial evaluation of the groups, blinding of the reviewers, acceptance of intervention, and analysis and presentation of results. Measurements of at least one key outcome were obtained in more than 85% of the subjects initially distributed per groups.…”
Section: Quality Analysis and Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation